Nanostructure Formation Leading To Modify the Optical Absorption of Gaq3 Thin Films - Muhammad, Fahmi F.; Sulaiman, Khaulah (Science Journal of University of Zakho, 2013)
This paper reports on the preparation of nanostructure along tris(8-hydroxyquinoline) gallium, Gaq3 thin film aiming at modifying its optical absorption property. The formation of nanostructure was achieved by means of thermal annealing in the temperature range from 85 oC to 255 oC under a flowing nitrogen gas for 10 minute. The results showed a modified optical absorption at 235 oC to produce a broad absorption spectrum which is quite wider than that of pristine film. It was noticed from the results of x-ray diffraction, XRD and field emission scanning electron microscopy, FESEM techniques that such annealing process has led to the formation of amorphous nanorods at specific temperatures, thereby modulating the films optical absorption. The relatively decreased absorption intensity at 255 oC was attributed to the partial crystalline formation and degraded nanostructures due to hard heating. Finally, the nanostructure growth was seen to possess a unique feature in modifying the optical behaviours of the Gaq3 thin films.